A Novel Immunobiotics Bacteroides dorei Ameliorates Influenza Virus Infection in Mice - Song, Liqiong; Huang, Yuanming; Liu, Guoxing; Li, Xianping; Xiao, Yuchun; Liu, Chang; Zhang, Yue; Li, Jintong; Xu, Jianguo; Lu, Shan; Ren, Zhihong (Frontiers in Immunology, 2022)
Objective Probiotics can modulate immune responses to resist influenza infection. This study aims to evaluate the anti-viral efficacy of B. dorei.. Methods Using a murine model of influenza infection, we evaluated the anti-influenza potency and underlying mechanism by measuring survival rate, lung viral load and pathology, gene expression and production of cytokines and chemokines, and analysis of gut microbiota. Results B. dorei was identified to have robust quercetin-degrading activity. The administration of B. dorei increased significantly (by 30%) the survivals of influenza-infected mice accompanied by obvious improvements in weight loss, lung pathology, lung index, and colon length compared to the vehicle control group. It reduced significantly (by 61%) the viral load of lung tissue and increased the expression of type 1 interferon more rapidly. In later stage of infection (7 days post infection), it decreased substantially the local (in lung)and systemic (in serum) levels of interferon and multiple proinflammatory cytokines or chemokines (IL-1β, IL-6, TNF-α, IL-10, MCP-1 and IP-10) to a comparable degree relative to the oseltamivi treatment. Administration of B. dorei also altered gut microbiota as indicated by increased levels of Bacteroides, Prevotella, and Lactobacillus and decreased levels of Escherichia, Shigella, and Parabacteroides. Conclusion B. dorei has anti-influenza effect and its working mechanisms involve promoting earlier interferon expression and down-regulating both local and systemic inflammatory response. B. dorei changes the composition of gut microbiota, which may also contribute to its beneficial effects.